2016
DOI: 10.5194/acp-16-7389-2016
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-burning impact on CCN number, hygroscopicity and cloud formation during summertime in the eastern Mediterranean

Abstract: Abstract. This study investigates the concentration, cloud condensation nuclei (CCN) activity and hygroscopic properties of particles influenced by biomass burning in the eastern Mediterranean and their impacts on cloud droplet formation. Air masses sampled were subject to a range of atmospheric processing (several hours up to 3 days). Values of the hygroscopicity parameter, κ, were derived from CCN measurements and a Hygroscopic Tandem Differential Mobility Analyzer (HTDMA). An Aerosol Chemical Speciation Mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 69 publications
5
89
2
Order By: Relevance
“…At the coastal sites in the Mediterranean (FIK) and Atlantic (MHD), 30 the non-refractory submicron aerosol particle mass is driven by inorganic components, predominantly sulfate. However, increased organic particle mass is observed during the biomass burning season at FIK (Bougiatioti et al, 2016), when κ reaches a minimum, and in springtime at MHD, as has been observed previously (Ovadnevaite et al, 2014 generally high owing to the influence of sea salt, but at the same time is also very variable owing to the mixed influences of marine organic aerosol and anthropogenic air pollution. Fig.…”
Section: Aerosol Chemical Composition and Composition-derived Hygroscmentioning
confidence: 72%
See 4 more Smart Citations
“…At the coastal sites in the Mediterranean (FIK) and Atlantic (MHD), 30 the non-refractory submicron aerosol particle mass is driven by inorganic components, predominantly sulfate. However, increased organic particle mass is observed during the biomass burning season at FIK (Bougiatioti et al, 2016), when κ reaches a minimum, and in springtime at MHD, as has been observed previously (Ovadnevaite et al, 2014 generally high owing to the influence of sea salt, but at the same time is also very variable owing to the mixed influences of marine organic aerosol and anthropogenic air pollution. Fig.…”
Section: Aerosol Chemical Composition and Composition-derived Hygroscmentioning
confidence: 72%
“…At BRW, the influence of Arctic Haze is evident from the higher CCN number concentrations in late winter and spring (Barrie, 1986). Also at FIK, the seasonal cycle is characterized by pollution events occurring in summer that are 5 associated with long-range transport of biomass burning aerosol containing larger size particles and absence of precipitation (Bougiatioti et al, 2016). The coastal sites at the Atlantic (MHD) and Pacific (NOT) show relatively large variability in all measured parameters without exhibiting a distinct seasonal cycle.…”
Section: Frequency Distributions Seasonal Cycles and Persistencementioning
confidence: 99%
See 3 more Smart Citations